Bargaining with the devil When to Negotiate, When to Fight - Mnookin, Robert (New York, 2010)
One of the country$1 (Bs most eminent practitioners of the art and science of negotiation offers practical advice for the most challenging conflicts$1 (Bwhen you are facing an adversary you don$1 (Bt trust, who may harm you, or who you may even feel is evil. This lively, informative, emotionally compelling book identifies the tools one needs to make wise decisions about life$1 (Bs most challenging conflicts.s
Keywords: Negotiation